LAJU OKSIDASI LEMAK DAN MUTU ORGANOLEPTIK IKAN TERI NASI KERING (Stolephorus spp) SELAMA PENYIMPANAN DINGIN - A. Suhaeli Fahmi; Widodo Farid Ma'ruf; Titi Surti (LPPM Universitas Pekalongan, 2014)
Polyunsaturated fatty acids are valuable nutritional content to be kept in fish. Polyunsaturated fatty acids are easily oxidized, so it can be easily rancid. Moreover lipid oxidation can cause damage to other food components because lipid oxidation produces reactive, toxic and carcinogenic compounds. This paper attempts to analyze the effect of dryingto the oxidation rate of dried anchovy. This research used Peroxide Value (PV) to measure the oxidation rate. The results showed thatduring chilled storage, PV had irregular pattern, because peroxide is a reactive and derivable compound. Sensory test showed that at the end of storage (28 days), the dried anchovy was still accepted by panels. Keywords :dried anchovy, lipid oxidation, chilled storage,peroxide value